2008
DOI: 10.1021/ef700637s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Doping on the Initial Pyrolysis Chemistry of Cellulose Chars

Abstract: Laser pyrolysis (LP) using a CO2 laser was used to rapidly heat Avicel cellulose char with and without doping by Na, K, Ca, Mg, Co, Ni, Cu, Pd, and Zn as their respective acetates in the uncharred cellulose. LP−molecular beam mass spectrometry (LP−MBMS) was used to probe the chemistry of the pyrolysis of the chars and to characterize the initial volatilized reacting plume of pyrolyzate. The mass spectra were deconvoluted by multivariant factor analysis (MVA). MVA revealed that, at the 1 wt % doping level, Cu d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The work in this study continues investigations from this laboratory involving the thermochemical conversions of biomass and its constituents [27]. There were three particular objectives in the current study.…”
Section: Introductionmentioning
confidence: 92%
“…The work in this study continues investigations from this laboratory involving the thermochemical conversions of biomass and its constituents [27]. There were three particular objectives in the current study.…”
Section: Introductionmentioning
confidence: 92%
“…High catalytic efficiency is typically expected with metal or metal oxides nanoparticles. 727 A great deal of fundamental work has been carried out on the addition of metal species to biomass by impregnation with metal salts solutions, which can explain the role of minerals during pyrolysis of biomass, 728-732 modify primary pyrolysis and increase selectivity towards one or more specic products, [729][730][731][732][733][734][735][736][737] or study the effect of re retardants. 737 It is well known that the presence of inorganic species dispersed in biomass can inuence the behavior of pyrolysis and thereby the distribution of pyrolysis products.…”
Section: Energy Applicationsmentioning
confidence: 99%
“…Kawamoto et al [33] observed that levoglucosan undergoes secondary reactions in the presence of cellulose-derived pyrolysis vapors. Recently, catalytic pyrolysis of cellulose [34][35][36] has widely been investigated with the goal of preparation of a specific product from cellulose. Dobele et al [20][21][22] studied the dehydration reactions of cellulose in the presence of phosphoric acid and high levoglucosenone yield was achieved, while levoglucosan formation was hindered.…”
Section: Introductionmentioning
confidence: 99%